Tinjauan Lingkungan Fisik Pada Madrasah Aliyah Al Muslim Ambon - Safna Kaplale; Vera Paulin Kay; Kalsum Lussy; Simson Melmambessy (P3M Politeknik Negeri Ambon, 2024)
The purpose of this writing is to be able to find out how the adequate physical work environment in